THE EFFECT OF MUDHARABAH, MUSYARAKAH AND MURABAHAH FINANCE ON THE PROFITABILITY OF SHARIA GENERAL BANKS IN INDONESIA IN 2013-2017 - Yogi Bayu Pratama; Erwin Febriansyah (BIMA Journal (Business, Management, & Accounting Journal), 2020)
This study aims to analyze the effect of mudharabah, musyarakah and murabahah financing on the level of profitability at Islamic Commercial Banks in Indonesia using the Return on Assets (ROA) ratio. The research method used is descriptive quantitative research approach and case studies at Islamic Commercial Banks in Indonesia. The type of data obtained from this research is secondary data based on the results of Sharia Commercial Bank financial reports which include BCA Syariah, BNI Syariah, BRI Syariah, Mandiri Syariah Bank, Syariah Bukopin and Muamalat Bank during the 2013-2017 period. Sources of data obtained through the results of publications from the relevant Islamic Commercial Bank and through the official website of each bank. The analytical tool used is multiple linear regression analysis.The results showed that Mudharabah and Mutanaqisah financing had a significant influence on ROA levels while financing for Murabahah had an insignificant effect on the partial ROA level. Simultaneously, this Mudharabah, Mutanaqisah and Murabahah financing has a significant influence on the level of ROA